Kongsberg Vision Meeting 2013: Abstracts - Baraas, Rigmor C; Einevoll, Gaute T. (Scandinavian Journal of Optometry and Visual Science, 2013)
Kongsberg Vision Meeting was arranged at Buskerud University College in Kongsberg for the sixth time on December 10, 2013. Rigmor C. Baraas and Gaute T. Einevoll organized the meeting. Keynote speakers were Michael Crossland from Anglia Ruskin University and Moorfields Eye Hospital, London (UK), and James A. Bednar from the University of Edinburgh (UK). The abstracts from the talks are presented in the order they were given.